Care Transitions Workshop for First-Year Medical Students - Manuel Eskildsen; Jonathan Flacker (Association of American Medical Colleges, 2010)
Abstract Introduction This resource is an interactive workshop related to care transitions in the older adult. It is meant for use with first- or second-year medical students who have not yet started their clinical rotations. Methods The materials include online cases and a PowerPoint lecture. Each case consists of a clinical scenario in which an older adult has had a difficult transition from one setting of care to the other: in the first, from hospital to home, and in the second, from hospital to skilled nursing facility. In each case, students are assigned to take on the role of one of the possible stakeholders in the scenario: hospital physician, receiving physician, case manager, and patient/family. For each role, students are asked to answer questions and to interact with their classmates who occupy different roles. This resource was originally implemented using an online discussion board format, but it can be used in small groups as well. Results We obtained 146 evaluations from our first-year medical school class. Students first completed a numerical evaluation using a 5-point Likert scale to rate seven questions addressing appropriateness of learning objectives, organization of session, effectiveness of teaching materials, presenter's skill in making the session enjoyable, and whether they would recommend future classes by the instructor. The composite Likert score for all the questions was 3.9. Discussion The AAMC released a set of geriatrics competencies in 2008 for all graduating medical students. Among these is competency 25: Communicate the key components of a safe discharge plan (e.g., accurate medication list, plan for follow-up, including comparing/contrasting potential sites for discharge). These materials provide an interactive resource for a topic that may be difficult to cover in lectures or during clinical rotations; they also can help students achieve one of the AAMC geriatric competencies.